The Effect of The Asean Economic Community on Household Income in Indonesia: - Farida Rohmah (ProBisnis : Jurnal Manajemen, 2022)
This study aims to analyze the impact of government investment in the trade sector carried out in preparation for the Asean Economy Community on the distribution of household income. “Simulation for Social Indicators and Poverty: IO and SAM Analysis” (SimSIP SAM). The first analytical tool used is to analyze export imports that occur in ASEAN countries against Indonesia using OLS Regression. This is done to see how the trade sector is happening in ASEAN countries as an impact of investment in the trade sector. After it is known that investment in the trade sector is known, then the analysis used is the Simulation for Social Indicators and Poverty: IO and SAM Analysis” (SimSIP SAM) to determine the multiplier impact that has occurred in Indonesia. The results of the analysis show that government investment of IDR 27 trillion in the trade sector has an impact on: (1) total household income reaching IDR 74 trillion or an increase of 1.94 percent;